Benefits of hypocrisy: Do managers gain more from greenwashing - Weixin Dong; Youcai Yang; Yan Chen (PLoS ONE, 2026)
This study finds that corporate greenwashing raises executive compensation. Mechanism analysis indicates that greenwashing enhances executive compensation by improving short-term performance and enhancing executive reputation. In addition, this effect is more pronounced in non-state-owned enterprises, companies with equity incentive plans, and firms that grant restricted stock.